The State of Working America - Gould, Anthony (Relations industrielles / Industrial Relations, 2014)
The State of Working America, by Lawrence Mishel, Josh Bivens, Elise Gould and Heidi Shierholz, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Central banks; Economic crisis; Employment; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z